In Good Times Prepare for Crisis : From the Great Depression to the Great Recession: Sovereign Debt Crises and Their Resolution - Lieberman, Ira W., 1942- (Book collections on Project MUSE., 2018)
Sovereign debt crises are a little like the weather: One can get ready to endure them and maybe take some steps to lessen their impact, but so far it hasn't been possible to prevent them. Like the weather, they just keep happening. That's the overriding thesis of this book tracing the major debt crises of the past century, starting with the Great Depression and running through the recent Great Recession. Written by a former World Bank expert on debt crises, this book discusses best practices for how such crises can be resolved. As the painful experience of the past decade reminded everyone, frequent debt crises and defaults do great damage to economies and cause vast personal hardship. But resolving them has proven difficult--both economically and politically--and has taken time, almost always requiring a lender of last resort such as a country's central bank or the International Monetary Fund. Too often, efforts to end debt crises have been little more than a palliative, and the debt overhang from one crisis contributes to the next, as illustrated by the ongoing saga in Greece. Both private and sovereign debts have increased substantially since the 2008 crisis, with inadequate deleveraging. This debt overhang leaves countries vulnerable and with limited maneuverability to address the next crisis. This book does not pretend to describe how debt crises can be prevented. But it does draw useful lessons from recent crises that can help economists, bankers, policymakers, and others resolve the inevitable future crises with the least possible damage. -- Provided by publisher.